DIFFERENTIATION OF BODY COMPOSITION OF PLAYERS OF THE POLISH NATIONAL BASEBALL TEAM - Jagiełło, Marina; Jagieło, Władysław; Kozina, Zh.L. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
The purpose of the study is to identify the differentiation of body composition among players of Polish national baseball team in comparison to persons of the same population not professionally engaged in sport. The study involved Polish baseball representatives (n=20). Competitors’ age was 18-28 years, body mass from 67.7 kg to 114 kg (85±10.3 kg), and body height 173-196 cm (185.1±4.8). The training experience was 7-14 years and it was highly differentiated. The stoutness factor is the dominant factor among "infielders" and "pitchers", and among "outfielders" - the length one. The proportions of the features within the factors show that players are characterized by a strongly muscled forearm and a shank and by a clear predominance of the elbow width with a disproportionately - to the overall size of the factor - small knee and shoulder width. In the length factor an even contribution of the upper and lower extremity length with lower sitting body height can be noted. Depending on the position on the field there is a differentiation of the internal proportions of the body.